Islamic banking practice : from the practitioner's perspective - Bank Islam Malaysia Berhad (Kaula Lumpur: Bank Islam Malaysia Berhad, 1994)
This is the first book published by Bank Islam in its series of efforts to educate the public on the teachings of Islam specifically on business transactions.
rpm 23/08/16
Loans
Keywords: Islamic banking; Banks and banking; Islamic countries; Banking law (Islamic law); Banks and banking - religious aspects - Islam